POBALIS LIDI Media Integrated with a Digital Interactive Guide for Batik Learning Mastery - Sugiantoro, Erfan; Sugianto, Alip; Mustikawati, Diyah Atiek (Journal of Innovation in Educational and Cultural Research, 2026)
Batik learning faces persistent challenges, particularly the scarcity of alternative instructional media and limited student engagement in the digital era. This study developed POBALIS LIDI, a hybrid media that integrates physical and digital elements to support students’ batik-making achievement in a valid, practical, and effective manner. The research employed a design-based research approach using the ADDIE model, involving fifth-grade students from a primary school in Indonesia. Data were collected through interviews, observations, questionnaires, and tests. The validity tests demonstrated that the media was highly valid, with material validation at 91.66%, media validation at 97.50%, and instructional validation at 93.75%. The media’s practicality was also rated highly, with a score of 90.33% based on positive user feedback. Implementation proved effective, as indicated by a one-sample t-test yielding p 0.001 and a Cohen’s d value of 1.687, indicating a large effect size. The average student learning outcome was 81.91, exceeding the minimum mastery criteria. This study concludes that the developed hybrid media successfully integrates authentic and digital learning experiences. The research contributes to educational technology by developing culturally grounded hybrid media that enhance adaptive learning in the digital era.